Reactivity of 3-Bromofuran in Pd-Catalyzed C–H Bond Arylation toward the Synthesis of 2,3,5-Triarylfurans - Sasmal, Arpan; Roisnel, Thierry; Bera, Jitendra K.; Doucet, Henri; Soulé, Jean-François (Synthesis, 2019)
Arylation of the C–H bond at the C2 position of 3-bromofuran is achieved using aryl bromides as coupling partners in the presence of phosphine-free Pd(OAc)2/KOAc in DMA. This procedure gives C2,C5-di- and even C2,C4,C5-triarylated 3-bromofuran derivatives when larger amounts of aryl bromides are employed. In addition, C2,C3,C5-triarylated furans—containing three different aryl groups—are synthesized via a C2–H bond arylation/Suzuki reaction/C5–H bond arylation sequence.
Keywords: palladium; furans; C–H bond arylation; aryl bromides